BRS A501 CL: herbicide-tolerant upland rice cultivar - Rangel,Paulo Hideo Nakano (2020)
Abstract BRS A501 CL is the first upland rice cultivar with tolerance to the broad-spectrum herbicide Kifix®. It has a medium-length cycle, high stability of whole grain yield at processing, good disease tolerance and a high grain yield.